Functional Nucleic Acids Under Unusual Conditions. (17th May 2021) - Chang, Tianjun; He, Sisi; Amini, Ryan; Li, Yingfu
Abstract: Functional nucleic acids (FNAs), including naturally occurring ribozymes and riboswitches as well as artificially created DNAzymes and aptamers, have been popular molecular toolboxes for diverse applications. Given the high chemical stability of nucleic acids and their ability to fold into diverse sequence‐dependent structures, FNAs are suggested to be highly functional under unusual reaction conditions. This review will examine the progress of research on FNAs under conditions of low pH, high temperature, freezing conditions, and the inclusion of organic solvents and denaturants that are known to disrupt nucleic acid structures. The FNA species to be discussed include ribozymes, riboswitches, G‐quadruplex‐based peroxidase mimicking DNAzymes, RNA‐cleaving DNAzymes, and aptamers. Research within this space has not only revealed the hidden talents of FNAs but has also laid important groundwork for pursuing these intriguing functional macromolecules for unique applications. Abstract : Unusual conditions, such as low solution pH, high and low temperatures, and organic solvents, were speculated to be the circumstances that ribozymes and riboswitches may have faced on the early Earth. Moreover, some artificial functional nucleic acids have been discovered to work under such unusual conditions and these molecules offer the potential for some interesting applications. Herein, we review recent progress of research on these functional nucleic acids.